Alternation preferences affect focus marking in German and English differently - Schauffler, Nadja (Frontiers in Psychology, 2023)
This study investigates the interplay between alternation preferences and corrective focus marking in the production of German and English speakers. Both languages prefer an alternation of strong and weak, and both use pitch accenting to indicate focus structure. The objective of the study is to determine whether the preference for rhythmic alternation can account for variations in the prosodic marking of focus. Contrary to what has been claimed before, results obtained from three production experiments suggest that rhythmic adjustment strategies do take place under focus marking. However, despite their similarity, the two languages rely on different strategies when alternation and focus marking are working in opposite directions. While German speakers often create a melodic alternation of high and low by realising the first of two adjacent focus accents with a rising pitch accent (L*H), English speakers often omit the first focus accent in clash contexts. This finding is corroborated by a second experiment investigating pitch accent clashes in rhythm rule contexts under different focus environments. The findings suggest that the preference for alternation can influence the prosodic marking of focus and is a source of variation in the realisation of information-structure categories.